2014
DOI: 10.1097/fjc.0000000000000096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nardostachys chinensis on Spontaneous Ventricular Arrhythmias in Rats With Acute Myocardial Infarction

Abstract: NC decreased the incidence of spontaneous ventricular arrhythmias (especially VF), reduced Cx43 degradation, and improved Cx43 redistribution in myocardial infarcted zone in rats with hyper-AMI. The data of the present study indicated that NC may be a promising drug in the future to prevent patients with AMI from lethal ventricular arrhythmias in prehospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…We included 16 studies in this review [ 19 – 34 ]. Among them, 12 studies were published in Chinese journals, [ 19 , 23 , 24 , 26 – 34 ] and 4 studies were published in English-language journals [ 20 – 22 , 25 ]. Five studies were associated with animal experiments [ 19 , 20 , 23 – 25 ], and 11 studies were related to cell experiments [ 21 , 22 , 26 – 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We included 16 studies in this review [ 19 – 34 ]. Among them, 12 studies were published in Chinese journals, [ 19 , 23 , 24 , 26 – 34 ] and 4 studies were published in English-language journals [ 20 – 22 , 25 ]. Five studies were associated with animal experiments [ 19 , 20 , 23 – 25 ], and 11 studies were related to cell experiments [ 21 , 22 , 26 – 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 12 studies were published in Chinese journals, [ 19 , 23 , 24 , 26 – 34 ] and 4 studies were published in English-language journals [ 20 – 22 , 25 ]. Five studies were associated with animal experiments [ 19 , 20 , 23 – 25 ], and 11 studies were related to cell experiments [ 21 , 22 , 26 – 34 ]. 4 studies reflected the reported cardioprotective effects of NC [ 19 – 22 ], including 2 studies based on cell experiments [ 19 , 20 ] and 2 studies based on animal experiments [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations